HOW PHYSICAL ACTIVITIES INFLUENCE ON SCHOOL TEACHERS' WORKING CAPACITY: THE RESEARCH RESULTS OF THE EXPERIMENT - Olga V. Yurechko; Andrey V. Leifa (Высшее образование в России)
The article describes the results research aimed at revealing the influence of physical activities on subject teachers' working efficiency.The research included an experiment with a control group and an experimental group of teachers at the age about 39 without health problems. The different elements of physical activities were introduced over the period of school year. On completion of the experiment we have accomplished the control measurements using the Harvard step test. The experimental group has demonstrated the reliably better results regarding mental working capacity.